2015
DOI: 10.4236/wjm.2015.59016
|View full text |Cite
|
Sign up to set email alerts
|

Joule Heating and Thermal Radiation Effects on MHD Boundary Layer Flow of a Nanofluid over an Exponentially Stretching Sheet in a Porous Medium

Abstract: A numerical study on boundary layer flow behaviour, heat and mass transfer characteristics of a nanofluid over an exponentially stretching sheet in a porous medium is presented in this paper. The sheet is assumed to be permeable. The governing partial differential equations are transformed into coupled nonlinear ordinary differential equations by using suitable similarity transformations. The transformed equations are then solved numerically using the well known explicit finite difference scheme known as the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…In order to check the validity of current solutions a comparison is carried out between present results and the results given in Rudraswamy and Gireesha [44], Anand Rao et al [45], Meraj Mustafa et al [46] and Anuar Ishak [47]. This comparison is shown in the tables 1 and 2 where a fine conformity has noticed in both results and hence ensured the validity of current results.…”
Section: Solving'supporting
confidence: 61%
“…In order to check the validity of current solutions a comparison is carried out between present results and the results given in Rudraswamy and Gireesha [44], Anand Rao et al [45], Meraj Mustafa et al [46] and Anuar Ishak [47]. This comparison is shown in the tables 1 and 2 where a fine conformity has noticed in both results and hence ensured the validity of current results.…”
Section: Solving'supporting
confidence: 61%
“…This study is an extension of work done by [4,5], Bachok et al [7] and Adnan et al [41]. The purpose of this study is to propose a new model that investigates the behavior of the flow and heat transfer for an unsteady stagnation-point flow over an exponential stretching/shrinking sheet in the presence of suction/injection and the velocity slip parameter immersed in nanofluid.…”
Section: Introductionmentioning
confidence: 92%
“…The physical quantities of interest are the local skin friction coefficient C f and local Nusselt number Nu x , which are given by Equation 14(see Rao et al [5]):…”
Section: Of 18mentioning
confidence: 99%
See 1 more Smart Citation
“…Yadav and Sharma [15] investigated the effect of Joule heating on MHD flow due to exponentially moving stretching sheet in porous media. Rao et al [16] reported the heat and mass transfer characteristics of a nanofluid over an exponentially stretching sheet in the presence of Joule heating. Adeniyan and Adigun [17] reported that an increase in the value of Eckert number increases the thickness of the thermal boundary layer.…”
Section: Introductionmentioning
confidence: 99%